Egyptian media, King Hussein, Baghdad Pact, Gamal Abdel Nasser, Britain. - Jaed, Hawraa Ward (Thi Qar Arts Journal, 2024)
After World War II, the Middle East witnessed the formation of military and political alliances, initiated by the United States. These alliances marked the end of bilateral treaties between countries. The formation of the Baghdad Pact was among these alliances, which ended the Anglo-Iraqi Treaty. However, this pact faced strong opposition from Egypt, which used media tactics to pressure Arab peoples and governments to avoid joining the pact. This strategy was largely successful, with Jordan being the most eager kingdom to join, but Egyptian media pressure prevented it.The study of Arab relations holds historical and political significance as it provides valuable information for both specialized Arab researchers and readers interested in the patterns and developments of foreign policy and its impact on overall Arab political and diplomatic relations. Analyzing these relations and the mechanisms governing them, as well as the resulting outcomes, indicates the strength or weakness of political ties among Arab countries. The topic of the Anglo-Jordanian Treaty and Egypt’s role in its termination highlights the political, military, and diplomatic connections between Arab countries at that time. This treaty caused many problems for Jordan in its foreign relations with all Arab countries, especially Egypt, as President Gamal Abdel Nasser was a major advocate for ending British dominance over Egypt, Jordan, and all Arab countries.